Clarification of the Functional Role of Appellate and Cassation Instance in the Light of the New Constitutional-legal Status - Sujyan , T. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The issues of ambiguous interpretation of the legislative regulations of appeal and cassation as forms of the judicial review, due to the lack of clear differentiation of the functional role of appeal and cassation, are discussed in the article presented. The article analyzes the new legal status of the Appellate and Cassation Courts and as a result of the analysis conclusions are made in regard to the possible legislative regulations in procedural laws aimed to guarantee the functional role of appeal and cassation.